Physiology and Pathophysiology of Proteinase-Activated Receptors (PARs): PAR-2-Mediated Proliferation of Colon Cancer Cell - Masahiro Nishibori; Shuji Mori; Hideo K. Takahashi (Elsevier, 2005)
Proteinase-activated receptor-2 (PAR-2) has been demonstrated to be highly expressed in the gastrointestinal tract. In the present minireview, we summarize the effects of PAR-1 and PAR-2 stimulation using their activating peptides and agonist proteinases on the calcium signaling and the cell proliferation in DLD-1 cell, a human colon cancer cell line. PAR-2 but not PAR-1 stimulation induced the enhancement of cell proliferation, whereas both PAR-1 and PAR-2 stimulation induced the transient increase in [Ca2+]i. PAR-2 stimulation induced the phosphorylation of MEK1/2 and ERK1/2, but PAR-1 stimulation did not. The inhibition of MEK1/2 by PD98059 completely abolished the proliferative response to PAR-2 stimulation. Thus, MEK-ERK activation plays major role in the PAR-2-mediated proliferative response. The coupling of PARs to calcium signaling and MEK-ERK activation may be independent, and varied dependent on cell types. Keywords:: proteinase-activated receptor, colon cancer, proliferation, mitogen-activated protein kinase